New opportunities with renewable energies - Programa Alianza en Energía y Ambiente con la Región Andina (AEA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
Communities value and take advantage of nature to generate renewable energy, improving their well-being and promoting sustainable development. They use technology to transform natural resources into clean energy, all participating in the creation of new opportunities for growth and inclusive businesses that improve the quality of life.